CLINICAL ASSESSMENT OF THE EFFICIENCY OF THE APPLICATION OF THE IMPROVED TECHNIQUE OF MANUFACTURING PLASTIC BASES OF REMOVABLE DENTURES - O. A. Kryvchuk (Ukrainian Medical Stomatological Academy, 2019)
Complete removable dentures remain one of the most popular types of prosthetics in Ukraine. Despite this, their effectiveness remains insufficient, due to the poor influence of plate bases made of acrylic plastics. It is proposed to improve the technology of making bases of removable dentures from acrylic plastics in two directions: firstly, by modernizing the method of pressing acrylic plastics, and secondly, by applying coating on the inner surface. The purpose of the research is to develop a clinical examination of the advanced technique for the manufacture of plate bases of removable dentures in edentulous patients. Materials and methods of the research. Clinical testing was carried out among 30 patients of middle and elderly age (60-82 years old), equal to men and women, with complete absence of teeth, who were made of two sets of removable dentures on both jaws (one by traditional method, another - by own one). The originality of the technique consisted of the application of a self-made construction of bugel, and applying a solution of polyvinyl alcohol for covering of inner surface of dentures. To evaluate clinical effectiveness, it was used the results of a clinical examination, in particular study of the mucous membrane of the prosthetic bed, and the evaluation of the functional efficacy of the prosthesis after 1 and 6 months after the delivery of the prosthesis. Results of the research and their discussion. With the use of a bugel of the original design, the thickness of the plastic lattice was 0.15 ± 0.05 mm, while it was 0.75 ± 0.20 mm when using the traditional method of pressing (p˂0.05). The application of the improved technique allowed reducing the number of cases of mucosal damage after 1 month of use of dentures to 20.0 ± 7.3% versus 30.0 ± 8.4% with traditional technology (р˂0.05). However, after 6 months, no reliable differences between the state of the mucous membrane for dentures manufactured according to different technologies were been established (p> 0,05). After 1 month of use of dentures made according to the traditional technology, the first level of stability (good fixation, characterized by the displacement of the complete removable prosthesis within the softness of soft tissues with the preservation of the closing valve) was recorded in 90.0 ± 5.5% of observations, and for improved - in 93.3 ± 4.6% (p> 0.05). The number of corrections was 3.5 ± 0.5 visits when applying traditional technology of the plastic bases, and for the improved one it was 2.1 ± 0.2 (p <0.05). Also, greater chewing efficiency is established for dentures, the bases of which were made according to the advanced technology, was 51.2 ± 1.6% against 46.8 ± 1.5% in 1 month and 60.5 ± 1.8% against 55.3 ± 1.6% after 6 months (p˂0.05). The difference between time of chewing for two series of dentures was not reliable (p <0.05). Conclusions. The use of the advanced technique for the manufacture of plate bases of complete removable dentures allows achieving a better state of the mucous membrane of the oral cavity after 1 month of using dentures, which is associated with a decrease in the toxic effects of the residual monomer. The best parameters of the functional efficacy of the prostheses can be explained by a more pronounced balance due to the lack of the lattice and, consequently, greater precision of the occlusal contacts of the dentures, which ensures better fixation and stabilization, and therefore creates optimal conditions for functioning. Prospects for further research. The obtained results give an opportunity to recommend the application of the advanced method for the prosthetics of defects in dentitions with removable dentures with bases made of acrylic plastics.